Geographical Isolation in the Protection of Human Rights for Remote Indigenous Communities (KAT) in Indonesia: Challenges in the Implementation of International Human Rights Law - Sutiarnoto; Juvito Solange Damanik; Vita Cita Tarigan (Talenta Publisher, Universitas Sumatera Utara, 2025)
Indonesia’s extensive forests and mountainous terrain result in significant geographical isolation for parts of its population, particularly Remote Indigenous Communities (Komunitas Adat Terpencil/KAT). This study examines the relationship between geographical isolation and the implementation of international human rights law in protecting the rights of KAT in Indonesia, as well as the normative and practical obstacles faced by the Indonesian government. Employing a normative and descriptive legal research method based on secondary data, this research analyzes international human rights instruments, particularly the UDHR, ICCPR, ICESCR, and ICERD, alongside Indonesian legal frameworks. The study finds that geographical isolation substantially hinders the practical realization of human rights for KAT, including the rights to an adequate standard of living, social security, and political participation. Limited accessibility restricts public services, economic development, legal oversight, and democratic processes in remote areas. Normatively, inconsistencies arise from differing national and international conceptions of indigenous peoples, where Indonesian law emphasizes socio-economic vulnerability and empowerment, while international law frames indigenous peoples as vulnerable rights-holders entitled to self-determination. The research concludes that greater harmonization between national law and international human rights standards, combined with policies addressing geographical isolation through environmental protection and equitable economic development, is essential for effective protection of KAT in Indonesia.